Marine alginate oligosaccharides – A promising biomaterial: current use and future perspectives in food industry and pharmaceutical applications - Cuong, Tran Van; Thoa, Nguyen Thi; Duwoon, Kim (Vietnam Journal of Science and Technology, 2018)
Alginate oligosaccharides (AOS) have been known as a natural material with a wide variety of biological activities, which used for a long time. The evidence of using AOS to confer health benefits have been documented. The isolation and characterization of the properties, biological activity as well as the applications of AOS in various fields have been studied recently. In present work, we provide the recent research of AOS, particularly focusing on the applications in food and medicinal industry. This review also describes some experimental models, application and discuss the functional and biological mechanisms of AOS. In conclusion, AOS promotes beneficial effects on the immuno-metabolic response to various infectious diseases as well as it is promising as a biomaterial for functional foods and medicinal drugs development.